Strategic Management to Improve Human Resources in Islamic Educational Institutions - Chusnul Khotimah Setya Darna; Andi Arif Rifa’i (Penerbit Hellow Pustaka, 2026)
Education plays a crucial role in the advancement of a nation, particularly in the context of Islamic educational institutions, which not only impart worldly knowledge but also instill religious values to shape noble character. To achieve the ideal educational goals, Islamic educational institutions require effective strategic management focused on improving the quality of human resources (HR). Strategic management can help organize the necessary steps to achieve quality education goals, as well as build a competitive advantage in educational institutions. This study aims to analyze the implementation of strategic management in enhancing HR quality in Islamic educational institutions. Using a literature review method, this research examines theories related to strategic management, HR management, and educational development in the Islamic context. The study also explores the vital role of teachers in creating excellent education through professionalism and appropriate competencies. The findings of this study are expected to provide insights for the sustainable development of management in Islamic educational institutions and contribute to improving the quality of education and HR in these institutions.